Classification of Protein Structures Using Deep Learning Models - Mirceva, Georgina; Naumoski, Andreja; Kulakov, Andrea (IEEE, 2022)
Protein molecules are very important in the organisms because they participate in different processes. Understanding the way they interact in the cells is of high importance. In order to understand that, solving the task of protein classification could be really helpful thus providing valuable knowledge about the similar proteins that belong to same class. In this paper we focus on solving the task of protein classification. First, we extract some features of the proteins thus obtaining feature vectors, and then by using deep learning architecture, we create prediction model that could be used for classifying protein structures. We present some experimental results of the obtained classification models.
Keywords: protein structure; protein classification; feature extraction; deep learning